Normese el codigo de niñez y adolescencia, el acuerdo de los progenitores en el pago de las pensiones alimenticias para que puedan ser reconocidas - Lizaldes Olmedo, Oscar Paul (2014)
The maintenance obligations and the recognition of parentage, integral elements of responsible parenthood, a concept which, however, does not end there, represent some of the most important topics in the field of the administration of justice in our country as the failures and absences in the mechanisms that ensure these duties constitute a violation of the rights of girls and boys, and one of the variants of economic violence and emotional that most frequently suffer from the Ecuadorian women. The equal access to justice is an essential human right of compliance in a democratic system, because when one or other rights are being violated, is the primary means to claim their compliance with the appropriate courts and ensure the equality of all persons before the law, which means that the State's obligation is to create the legal conditions and materials to ensure its validity in conditions of equality, in this case both of the alleged parents, and parents of the minors. The effective guarantee of the duties of responsible parenthood in Ecuador, which includes both the protection of the rights as the existence of mechanisms to ensure compliance with the law, in this particular case, it would be helpful to know the way in which the legislation and the competent institutions competent guarantee the fulfilment of the duties of responsible parenthood, and building the configuration of the responsible parenthood in the Ecuadorian law, analyzing the actions of institutions responsible for the care of the duties of fatherhood for the integral development of the family, on the basis of their ideas, experiences and perceptions on fatherhood, to ensure compliance with the duties of demographics and economic assistance.